2016
DOI: 10.1002/pat.3772
|View full text |Cite
|
Sign up to set email alerts
|

Self-reinforced composites based on commercial PP woven fabrics and a random PP copolymer modified with quartz

Abstract: Self-reinforced composites based on commercial polypropylene (PP) woven fabrics and a random PP copolymer modified with quartz were obtained by film stacking. The effect of the incorporation of quartz on the materials fracture and failure behavior was studied through uniaxial tensile tests and quasi-static fracture experiments. Acoustic emission analysis was also performed in situ in the tensile tests. A higher consolidation quality was obtained for the composites containing quartz. In the composite with rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…was also used as reinforcement. In this fabric, a range of melting temperature between 173 °C and 178 °C was observed This result indicated that this fabric presented zones with different melting temperatures, as a result of the different stretching levels obtained during processing.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…was also used as reinforcement. In this fabric, a range of melting temperature between 173 °C and 178 °C was observed This result indicated that this fabric presented zones with different melting temperatures, as a result of the different stretching levels obtained during processing.…”
Section: Methodsmentioning
confidence: 71%
“…The results of the mechanical characterization of the woven PP fabric have been previously reported in another investigation . They are also included in this work only for comparison: maximum longitudinal and transversal stress values were 153.4 MPa and 117.4 MPa, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Kmetty et al proposed to use pre‐impregnated pellets, prepared by film‐stacking of high tenacity polymer fibres and copolymer matrix, serving as adequate starting material for injection moulding of SRPCs with homogeneous fibre distribution and improved mechanical properties . Recently, researchers also drew attention to the advantages of using organic and inorganic fibres and fillers in SRPCs, but the feasibility of such hybrid composite preparation with the injection moulding technology was not yet studied.…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of SPCs was first proposed by Capiati and Porter, [ 4 ] a variety of methods for preparing SPCs have been developed, including film stacking, [ 8, 9 ] solution/powder impregnation, [ 10, 11 ] hot compaction, [ 12, 13 ] co‐extrusion, [ 14, 15 ] sintering, [ 16 ] extrusion‐calendering [ 17 ] and injection molding (i.e., injection molding using pre‐impregnated SPC pellets [ 18, 19 ] and injection molding on an insert [ 20, 21 ] ). All these approaches can be classified as physical forming methods.…”
Section: Introductionmentioning
confidence: 99%